P0857BURDEN OF ANEMIA ASSOCIATED WITH CHRONIC KIDNEY DISEASE IN DIALYSIS AND NON-DIALYSIS-DEPENDENT PATIENTS IN EUROPE: A REVIEW OF PUBLISHED EVIDENCE. (6th June 2020) - Okoro, Tony; Amelio, Justyna; Mahajan, Anadi; Gupta, Digant; Refoios Camejo, Rodrigo
Abstract: Background and Aims: Anaemia is a frequent complication in patients with chronic kidney disease (CKD). The aim of this literature review was to understand the prevalence and burden of anaemia associated with CKD, with a further focus on Europe. Method: A targeted literature review was conducted to identify publications on prevalence estimates (search: January 2015 to August 2018), and a systematic literature review was performed to identify publications on humanistic and healthcare resource use (HRU) burden (search: from database inception to July 2018) using MEDLINE ®, Embase ®, Cochrane Library, and conference proceedings. These were complemented by grey literature searches. Citations were screened per predefined criteria to include observational studies and reviews. Case series/reports and conceptual model studies were excluded. The study population included patients with anaemia associated with CKD, irrespective of CKD stage, dialysis status, or modality. All searches were funded by GSK. Results: After applying all inclusion and exclusion criteria, 18 publications were retained that contained prevalence data, of which 9 provided European data. Based on 9 publications, the prevalence of anaemia associated with CKD in European adults was reported to range from 12.8% to 61.5% (Figure). Prevalence was higher in older individuals (aged >60 years) and increased with more advanced CKD stages. However, the methodology used to identify anaemia was not consistent across studies. Anaemia was identified based on varying thresholds of haemoglobin (Hgb) levels per different clinical guidelines (Kidney Disease Improving Global Outcomes [KDIGO], N=4; World Health Organization [WHO], N=2; European Best Practice Guidelines [EBPG], N=3), use of anaemia treatment, or Hgb thresholds without a reference to a specified guideline. Most studies focused on later-stage CKD patients (3 − 5), with only 2 studies reporting rates for stage 1 and 2 patients. A total of 50 publications provided data on humanistic and HRU burden, 6 of which provided European data. The literature on humanistic and HRU burden showed adults with anaemia associated with CKD had significantly poorer health-related quality of life (HRQoL) compared with those without anaemia, with significantly lower Kidney Disease Quality of Life (KDQoL) scores reflecting poorer HRQoL observed in the following domains: symptoms/problems, effect of kidney disease, and burden of kidney disease. This finding was consistent irrespective of instrument used for HRQoL assessment. However, tools used were not specific to anaemia or anaemia associated with CKD, and publications did not mention whether thresholds for clinical meaningfulness had been identified and/or met. Publications on HRU in anaemia associated with CKD in Europe were sparse (N=1): this single published study reported increased HRU in CKD patients with anaemia compared with CKD patients without anaemia. Conclusion: Prevalence rates of anaemia associated with CKD reported in Europe vary, with increased prevalence in later stages of CKD. Anaemia negatively impacts patient QoL and leads to increased HRU in patients with CKD. More data are needed to characterise anaemia in earlier stages of CKD and across different populations (e.g. patients with particular comorbidities or undergoing different types of dialysis) in European countries. Due to varied definitions of anaemia, it would be of interest to evaluate the extent of underdiagnosis and its impact on prevalence rates.